Libera Informazione Geografica in Italia - Redazione, Redazione (GEOmedia, 2008)
Free Geographic Information in Italy This GEOmedia issue features a new section dedicated to the world of free software and data and moreimportantly to the italian association for free geographical information better known as GFOSS.it. GFOSS.it, born in 2007, has already gathered the interest and the efforts of a wide community which made this association one of the more dynamic communities of the sector.